Factors affecting decision-making process in consumers purchasing behavior : case study Cosway multilevel marketing strategy / Violet Vivienne Louis - Louis, Violet Vivienne (2012)
Multi-level marketing is also known as network marketing , is an industry with its size and reputation are growing rapidly. According the Direct Selling Association (DSA), direct selling is a US$75 billion industry worldwide with an annual growth rate of around 10 per cent. The industry offers an alternative marketing channel to traditional retail selling that accommodates our changing marketplace. This case study is made to survey the preferences of consumers in choosing the ever increasing of the number of MLM products and the variety of goods available in the stokist stores compared to products at supermarkets or shopping malls. With the need of advance lifestyle of nowadays life trending, the existing market availability of multi-component of MLM products and supermarket products to the purchasing capabilities not only it has broadened the sphere of consumer choice, it also adds complication in making a purchase decision. The objective of this study is to identify the factors affecting influencing purchase decisionmaking process among consumers preferences to MLM products such as COSWAY in Kota Kinabalu and Keningau area. The respondent comprised of 100 male and female consumers among various age of populations. To achieve the objective of this study, efforts were done to identify the factors in influencing decision-making process among respondents based on gender, age, education level and job status, household income and marital status. Questionnaires were used as a method to collect the data. Frequency, percentage, Mann Whitney test were used to analysed the data. The results of the findings indicate the probabilities of the variables in investigating the related factors and it shows.